(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Analysis of the Role of Maize Commodities in the Regional Economy in Central Lombok. Maize is one of the world’s most important food crops besides wheat and rice. Central Lombok Regency is the highest corn producer in NTB Province. The purpose of this study: (1) To analyze whether the corn commodity is a base in the Central Lombok region, (2) To analyze the amount of regional revenue of Central Lombok Regency from corn commodities, (3) To analyze the role of corn commodities in regional development in Central Lombok. This research uses secondary and primary data. Data collection was done by documentation and analyzed by location quotient, acceptance and shift share methods. The results showed that corn commodity is a basic commodity with LQ value <1 so it becomes a non-basic commodity. Central Lombok Regency’s revenue from the corn commodity from the observation year fluctuated, the largest increase and the largest amount of revenue was in 2022 by 50.83% to Rp 356.5 million. The corn commodity in Central Lombok Regency has an important role in the economy of the Central Lombok Regency region, including the corn commodity contributing IDR 12.809,275 billion to the economy of Central Lombok Regency. To increase corn production, the Central Lombok Regency Government provides counseling and assistance to farmers.